2007
DOI: 10.1016/j.alcohol.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional gene expression differences between inbred alcohol-preferring and –non-preferring rats in five brain regions

Abstract: The objective of this study was to determine if there are innate differences in gene expression in selected CNS regions between inbred alcohol-preferring (iP) and -non-preferring (iNP) rats. Gene expression was determined in the nucleus accumbens (ACB), amygdala (AMYG), frontal cortex (FC), caudate-putamen (CPU), and hippocampus (HIPP) of alcohol-naïve adult male iP and iNP rats, using Affymetrix Rat Genome U34A microarrays (n = 6/strain). Using Linear Modeling for Microarray Analysis with a false discovery ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 92 publications
8
98
0
2
Order By: Relevance
“…Of the remaining 3 genes, Map1b changed in the same direction with both measures (however, the RT-PCR values were not statistically different), Camk4 was not changed in the RT-PCR measure, and Nrxn3 changed significantly in both measures, but in opposite directions (Table 7). Similar to previous studies from our lab (Edenberg et al, 2005;Kimpel et al, 2007), there was a high degree of concordance between the microarray and RT-PCR results. However, the lack of agreement between the two measures for Camk4 and Nrxn3 suggests the results for these two genes are inconclusive.…”
Section: Quantitative Rt-pcr Confirmationsupporting
confidence: 76%
“…Of the remaining 3 genes, Map1b changed in the same direction with both measures (however, the RT-PCR values were not statistically different), Camk4 was not changed in the RT-PCR measure, and Nrxn3 changed significantly in both measures, but in opposite directions (Table 7). Similar to previous studies from our lab (Edenberg et al, 2005;Kimpel et al, 2007), there was a high degree of concordance between the microarray and RT-PCR results. However, the lack of agreement between the two measures for Camk4 and Nrxn3 suggests the results for these two genes are inconclusive.…”
Section: Quantitative Rt-pcr Confirmationsupporting
confidence: 76%
“…The neuroimmune transcriptome & alcohol dependence: potential for targeted therapies Review identified immune and inflammatory transcripts and pathways in alcohol-exposed tissue from mice, rats and human tissue [3][4][5]34,[102][103][104]. Several immune genes found in these microarray studies were validated in rodent ethanol consumption paradigms, further corroborating a role for neuroimmune signaling in drinking behavior [14,105].…”
Section: Microglia Alcohol Activation Of Microglial Genesmentioning
confidence: 89%
“…Genetic analyses have an important role in identifying many immune-related genes associated with alcohol abuse in both rodents and humans (Kimpel et al, 2007;Liu et al, 2006;Mulligan et al, 2006). Validating several candidate genes from these studies (including Cd14, Il1ra, and Il6) through single-gene null mutations in mice confirmed that knockout of each gene resulted in decreased alcohol consumption on a two-bottle choice test (Blednov et al, 2012).…”
Section: Alcohol Glia and Neuroimmune Signalingmentioning
confidence: 91%